Privatising land in England. Issue 2 (8th July 2019) - Layard, Antonia
Abstract : Purpose: This paper aims to analyse the extent to which privatising – or denationalising land – has legal and policy effects. Design/methodology/approach: It applies the law in context scholarship to the question of land privatisation. Findings: Of all the recent privatisations in England, the most valuable, and yet least recorded, is of land. According to one estimate, two million hectares or 10 per cent of the Britain landmass, left the public sector for private ownership between 1979 and 2018. Privatisations include land that is sold, leased or where a public body changes its status. This paper aims to explore these privatisations, considering them as denationalisations, concluding that the effects are most significant in housing where the differences between social and private renting in relation to rents, the security of tenure and housing quality are striking. Moreover, although other public law restraints on the state-owned property are often limited, they are also still significant, facilitating scrutiny, particularly in combination with the public sector equality duty or site-specific duties for libraries, allotments or playing fields. All the sites disposed of to private developers, landlords and companies have lost these protections. Originality/value: This is the first time this question has been considered in this way from a legal perspective.